Implementation of the program comunicándonos orally to develop social skills in students of the VII cycle - Vivar-Justiniano, María N. (2019)
It is necessary that educational institutions as a socializing agent and social development agent, enhance and reinforce social skills in children. The aim of this study was to demonstrate the implementation of the program let us communicate orally enhances the development of social skills in the students. The research was applied and was held at experimental level and the experimental and control groups were considered who pretest and posttest were applied; also an intact group was considered for the respective matching. The sample was 50 students of high school distributed equitably for each study group. For the verification of the hypothesis t student was applied with calculated t value (2.50) higher the critical value (1.68). The results concluded that the development of social skills in students enhance through the implementation of the program, observing statistically significant differences in the results obtained.